Ultra-sensitive detection of ecologically rare fish from eDNA samples based on the RPA-CRISPR/Cas12a technology - Xing-Yi Wei; Li Liu; Huan Hu; Huang-Jie Jia; Ling-Kang Bu; De-Sheng Pei (iScience, 2023)
Summary: Environmental DNA (eDNA) research holds great promise for improving biodiversity science and conservation efforts by enabling worldwide species censuses in near real-time. Current eDNA methods face challenges in detecting low-abundance ecologically important species. In this study, we used isothermal recombinase polymerase amplification (RPA)-CRISPR/Cas detection to test Ctenopharyngodon idella. RPA-CRISPR-Cas12a detected 6.0 eDNA copies/μL within 35 min. Ecologically rare species were identified in the Three Gorges Reservoir Area (TGRA) using functional distinctiveness and geographical restrictiveness, with seven fish species (9%) classified as potentially ecologically rare including three species in this investigation. RPA-CRISPR/Cas12a-FQ outperformed high-throughput sequencing (HTS) and qPCR in detecting low-abundance eDNA (AUC = 0.883∗∗). A significant linear correlation (R2 = 0.682∗∗) between RPA-CRISPR/Cas12a-FQ and HTS quantification suggests its potential for predicting species abundance and enhancing eDNA-based fish biodiversity monitoring. This study highlights the value of RPA-CRISPR/Cas12a-FQ as a tool for advancing eDNA research and conservation efforts.